Observation of antiferromagnetic coupling in epitaxial ferrite films - SHVETS, IGOR; ARORA, SUNIL KUMAR (My University, 2006)
Defects in ferrite can change the local magnetic coupling from ferromagnetic to strongly antiferromagnetic. In eptiaxial magnetite (Fe3O4) films, defects locally altering exchange interaction, i.e., ?antiphase boundaries? (APB), essentially determine magnetic and magnetotransport properties. We locally observed specific magnetization reversal events in epitaxial magnetite Fe3??O4?MgO films (??0.03) by magnetic force microscopy in external magnetic fields. A dominating phenomenon is pinning of bubble domains at single APB. Pinning is a particular consequence of antiferromagnetic coupling across APB. Antiferromagnetic coupling across APB could be directly verified for a sample with an APB domain size above the resolution limit of magnetic force microscopy.
PUBLISHED
Keywords: Atomic, molecular and chemical physics; thin films